THE STUDY OF LAW ON INVESTMENT LIBERALISATION POLICIES IN THE REGION OF ASEAN AND THE EFFECTS ON INDONESIA - Yanti, Delfi (Faculty of Law, Universitas Sebelas Maret, 2017)
In order to realize a single ASEAN market through the free flow of investment in ASEAN, the ASEAN member states have agreed on the ASEAN Comprehensive Investment Agreement or known by the term ACIA signed in Cha-Am (Thailand) on February 26, 2009. The issue is how the rule of law against the liberalization of foreign investment in the ACIA Agreement and how its influence on Indonesia. This research method is a normative juridical research by using a qualitative data analysis technique. Based on the Article 1 (a) of ACIA related to the purpose of the establishment of ACIA the ACIA Agreement contains the legal concept of foreign investment: an investment regime that is